Acting against your own interests: The tension between emotion regulation preference and efficacy and its implications for individuals with depressive symptoms. - Rotem Vered (Public Library of Science (PLoS), 2021)
The aim of this study was twofold: first, to compare individuals' strategy choices in low and high intensity conditions and the actual efficacy of these strategies; second, to assess whether and how perceived intensity levels of aversive situations moderate the relationship between depressive symptoms and a strategies' efficacy. In Experiment 1A (N = 58), we replicated previous results, showing that individuals prefer distraction in high- and reappraisal in low-intensity conditions, irrespective of depressive symptom levels. Experiment 1B (N = 50) assessed the efficacy of distraction and reappraisal strategies in aversive conditions with low and high intensity. Contrary to our prediction, reappraisal was more effective than distraction, independent of the intensity of the aversive conditions. In Experiment 2 (N = 113), we tested the interactive relationship between perceived intensity levels and depression on the relative effectiveness of reappraisal and distraction. We found that while in perceived low-intensity situations the advantage of distraction over reappraisal increased as depressive symptoms increased, no such relationship was found in high-intensity situations. The results suggest that while all individuals prefer to apply reappraisal in both low- and high-intensity conditions, for those with high level of depressive symptoms, such a preference acts against their own interests. The study highlights the need to distinguish between emotion regulation preferences and their actual efficacy, while illuminating possible implications for individuals with depressive symptoms.